2019
DOI: 10.3390/nano9101392
|View full text |Cite
|
Sign up to set email alerts
|

Low Reflection and Low Surface Recombination Rate Nano-Needle Texture Formed by Two-Step Etching for Solar Cells

Abstract: In this study, needle-like and pyramidal hybrid black silicon structures were prepared by performing metal-assisted chemical etching (MACE) on alkaline-etched silicon wafers. Effects of the MACE time on properties of the black silicon wafers were investigated. The experimental results showed that a minimal reflectance of 4.6% can be achieved at the MACE time of 9 min. The height of the nanostructures is below 500 nm, unlike the height of micrometers needed to reach the same level of reflectance for the black s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the previous study, the J–V characteristics were performed under different passivation value without taking into account the lifetime degradation. On the other hand, the processes of the MACE leads to dislocations and dangling bonds resulting in a severe SRH recombination 79 . It was reported that the carrier lifetime strongly depends on the injection level and the MACE etching time 79 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, the J–V characteristics were performed under different passivation value without taking into account the lifetime degradation. On the other hand, the processes of the MACE leads to dislocations and dangling bonds resulting in a severe SRH recombination 79 . It was reported that the carrier lifetime strongly depends on the injection level and the MACE etching time 79 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the processes of the MACE leads to dislocations and dangling bonds resulting in a severe SRH recombination 79 . It was reported that the carrier lifetime strongly depends on the injection level and the MACE etching time 79 . Further, the carrier lifetime decreases by increasing the frontal surface area in practical 79 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For safeguarding optical instruments present on the satellites and to suppress stray light, various types of black coatings are developed in past few years . Most of these black surfaces are fabricated using surface texturing, optical grating, etching, nano composite or by applying coating of different nanomaterials on the surface of interest. It is observed that the surface texturing/etching followed by nano‐coating shows enhanced light trapping capacity in a broader wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates the advantages of superior light-trapping ability and structure characteristics for the new fabrication process to create b-Si solar cells. Naturally, the hybrid (joint) use of b-Si and pyramidal textured surfaces can get a more tangible effect [8].…”
mentioning
confidence: 99%